Z‐bpy, a New C2‐Symmetric Bipyridine Ligand and Its Application in Enantioselective Copper(I)‐Catalyzed Cyclopropanation of Olefins1. Issue 8 (20th June 2019) - Ouyang, Yizhao; Zhan, Miao; Zhou, Jing; Jiao, Jiao; Hu, Hao; Yamada, Yoichi M. A.; Li, Pengfei
Summary of main observation and conclusion: A rigid C 2 ‐symmetric chiral bipyridine ligand Z‐bpy with a triptycene‐like backbone was designed and synthesized from simple chemicals in a scalable route. Using this new ligand, copper(I) catalyzed cyclopropanation of styrenes with commercial ethyl diazoacetate produced various corresponding cyclopropanes in high yields, diastereoselectivity and enantioselectivity up to 97% ee . Abstract : A new C 2 ‐symmetric bipyridine ligand with triptycene‐like backbone was synthesized and used in highly efficient asymmetric cyclopropanation reaction with small reagent ethyl diazoacetate.